2009
DOI: 10.1111/j.1365-2605.2008.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of epithelial sodium channels improves sperm motility in asthenospermia patients

Abstract: Epithelial Na(+) channels (ENaCs) are ion channels that play important roles in physiology as well as pathophysiology. Inhibiting ENaCs using amiloride and its derivatives has been suggested in treatment of cardiovascular disease and hypertension. By immunoblotting, we demonstrated the presence of ENaC-alpha protein in the flagellar midpiece of both rat and human sperm. Immunohistochemistry analyses in rat testis localized ENaC-alpha expressed in the Leydig cell, Sertoli cell, Ap spermatogonium, spermatocyte, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…It might reflect abnormal sperm leakage to the SP and that Na/K flux needed for sperm metabolism is altered. Contrary to our results, previous studies in rats, humans, and boars, have shown that a sodium blockade increases extracellular sodium ions improving sperm motility [Kong et al 2009;Holt and Harrison 2002]. In these studies different compounds were added to the semen and this resulted in an increase in motility.…”
Section: Discussioncontrasting
confidence: 99%
“…It might reflect abnormal sperm leakage to the SP and that Na/K flux needed for sperm metabolism is altered. Contrary to our results, previous studies in rats, humans, and boars, have shown that a sodium blockade increases extracellular sodium ions improving sperm motility [Kong et al 2009;Holt and Harrison 2002]. In these studies different compounds were added to the semen and this resulted in an increase in motility.…”
Section: Discussioncontrasting
confidence: 99%
“…ENaC is a heteromultimeric channel that can be formed by the combination of four subunits: α, β, γ and/or δ, where α or δ formed the channel pore (57,58). In humans, previous reports demonstrated the presence of the ENaC-β subunit in testis (59), Hernández González and coworkers (28) mentioned the detection of ENaC-α in human spermatozoa and Kong and coworkers (60) showed the presence of ENaC-α by western blot and detected its presence in the midpiece of human sperm by immunocytochemistry, the same region as reported for CFTR (61)(62)(63)(64). The latter authors also showed that the treatment of human sperm with EIPA, an inhibitor of ENaC, improves sperm motility in both healthy donors and asthenospermic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot was carried out to evaluate the specificity of anti-peptide sera (from week 7) as previously described (25). Briefly, plasma membrane proteins of mouse testis and kidney (negative control) were extracted by using the plasma membrane protein extraction kit and subjected to 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis, transferred onto a nitrocellulose membrane, and incubated with anti-peptide sera at 1:1,000 dilution.…”
Section: Western Blotmentioning
confidence: 99%